HSF1 and HSPA6 as functional candidate genes associated with heat tolerance in Angus cattle. - BAENA, M. M. (2018)
The purpose of this study was to access and characterize single nucleotide polymorphisms (SNP) located within the HSF1 and HSPA6 candidate genes for adaptability in Angus breed raised in subtropical climate. Samples of DNA from 20 animals representing extreme phenotypes for adaptability traits were obtained. Sequence variations in the candidate genes were described by sequencing target regions. We identified 12 SNP located in the HSF1 gene. Moreover, four of the six SNP found in the HSPA6 gene cause amino acid substitutions in protein-coding regions. We also identified a representative SNP (called tag SNP) in a region of the HSF1 gene with high linkage disequilibrium (r2 = 0.87) that may represent 11 SNP located in this gene. Minor allele frequency observed for the SNP ranged from 0.10 to 0.50 and 0.02 to 0.21 for the HSF1 and the HSPA6 genes, respectively. Overall, almost all SNP analyzed showed significant deviation from the Hardy-Weinberg Equilibrium and half of the loci had heterozygosity greater than 0.50. The data suggest that there is sequence variability in these genes that could be exploited by breeding programs. There is genetic variation in HSF1 and HSPA6 genes in this populations of Angus breed, which is fundamental to obtain response to selection.